1986
DOI: 10.1111/j.1365-2125.1986.tb02876.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular toxicity and distribution kinetics of intravenous chloroquine.

Abstract: 1 Chloroquine diphosphate (3 mg base kg-1) was given by constant rate intravenous injection over 10 min to 12 healthy adult male volunteers. Plasma concentrations of chloroquine and the principal metabolite desethylchloroquine, electrocardiograph intervals, and arterial blood pressure were measured at frequent intervals to determine the relationship between cardiovascular effects and plasma concentrations.2 Peak plasma concentrations ranged between 784 and 6649 (mean 2913) ng ml-'. The decline in plasma concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 17 publications
5
51
0
Order By: Relevance
“…It remains the most widely used antimalarial agent although there is considerable concern surrounding its safety when given parenterally (WHO, 1984). Preliminary studies in volunteers (Gustafsson et al, 1983;Looareesuwan et al, 1986) showed that intravenous injection of chloroquine was potentially dangerous because of transient but very high, plasma chloroquine concentrations. It seemed likely that slow intravenous infusion of chloroquine would be safer.…”
Section: Discussionmentioning
confidence: 99%
“…It remains the most widely used antimalarial agent although there is considerable concern surrounding its safety when given parenterally (WHO, 1984). Preliminary studies in volunteers (Gustafsson et al, 1983;Looareesuwan et al, 1986) showed that intravenous injection of chloroquine was potentially dangerous because of transient but very high, plasma chloroquine concentrations. It seemed likely that slow intravenous infusion of chloroquine would be safer.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its extensive tissue distribution throughout the body, the total volume of distribution is extremely large (100 to 1,000 l/kg body weight) compared with the volume of central compartment (0.2 l/kg body weight) (Krishna and White, 1996). This explains the transiently high blood concentrations and wide peak to trough fluctuation after parenteral administration (Looareesuwan et al, 1986). Approximately 50 to 70% of CQ is bound to plasma protein mainly to alpha 1 -acid glycoprotein.…”
Section: General Pharmacokinetic Propertiesmentioning
confidence: 98%
“…In another two published articles (Na-Bangchang et al, 1994a;Hoglund et al, 2016), the relationship between clinical efficacy of the standard three-day CQ and the pharmacokinetics of CQ and DECQ were examined in patients with P. vivax infection to explain the cause of treatment failure in the light of accumulating evidence for the declining of in vitro sensitivity of P. vivax isolates in Thailand to CQ. Looareesuwan et al (1986) reported a transient but markedly high plasma CQ concentration in a preliminary study in healthy Thai subjects. Edwards et al (1987) further carried out a detailed study to confirm whether the change in CQ pharmacokinetics during P. falciparum infection was also a significant contributing factor to the severe cardiovascular adverse effects following treatment with intravenous administration of CQ.…”
Section: General Pharmacokinetic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations